2012
DOI: 10.1007/s00441-012-1456-y
|View full text |Cite
|
Sign up to set email alerts
|

Co-localisation of Kir4.1 and AQP4 in rat and human cochleae reveals a gap in water channel expression at the transduction sites of endocochlear K+ recycling routes

Abstract: Sensory transduction in the cochlea depends on perilymphatic-endolymphatic potassium (K(+)) recycling. It has been suggested that the epithelial supporting cells (SCs) of the cochlear duct may form the intracellular K(+) recycling pathway. Thus, they must be endowed with molecular mechanisms that facilitate K(+) uptake and release, along with concomitant osmotically driven water movements. As yet, no molecules have been described that would allow for volume-equilibrated transepithelial K(+) fluxes across the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 58 publications
3
32
0
Order By: Relevance
“…The inwardly rectifying potassium channel K ir 4.1 has been found in the SV, spiral ganglion and, recently, also in the supporting cells (Hibino and Kurach 2006;Eckhard et al 2012). K ir 4.1 is abundantly localized in the IMCs.…”
Section: Discussionmentioning
confidence: 98%
“…The inwardly rectifying potassium channel K ir 4.1 has been found in the SV, spiral ganglion and, recently, also in the supporting cells (Hibino and Kurach 2006;Eckhard et al 2012). K ir 4.1 is abundantly localized in the IMCs.…”
Section: Discussionmentioning
confidence: 98%
“…The pivotal role of strial melanocytes in the generation of the endocochlear potential is to secrete K + ions into the intrastrial space and hence they express the inward‐rectifying potassium channel KCNJ10 (also known as K ir 4.1, [MIM 602208]) (Ando and Takeuchi, 1999; Eckhard et al, 2012). In contrast to the potassium channels of the marginal cells, we did not observe any KCNJ10 expression in strial melanocytes up to the last stage we investigated, W18.…”
Section: Discussionmentioning
confidence: 99%
“…However, mutations in KCNJ10 itself have also been linked directly to Pendred syndrome (Yang et al, 2009). Interestingly, KCNJ10 has also been described in the root cells of the outer sulcus, both in the adult rodent and human cochlea (Jagger et al, 2010; Eckhard et al, 2012). Also, the expression pattern of KCNJ10 that we observed in the outer sulcus during cochlear development matches the known expression pattern of PENDRIN in the outer sulcus of the adult mouse cochlea (Royaux et al, 2003; Wangemann et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 47 studies examining AQP expression in the inner ear have been identified (Table ) . Of the 47 studies, 16 were in mice, 17 in rats, 17 in humans, and seven in other species.…”
Section: General Characteristics Of Aquaporinsmentioning
confidence: 99%
“…In addition to mice, rats, and humans, there were five studies using guinea pigs, two studies using Mongolian gerbils, one study using zebrafish, and one study using leopard frogs . Of the studies conducted in humans, seven cases analyzed tissues obtained from the vestibular schwannoma, three cases analyzed tissues from the meningioma, and two cases analyzed the ES from patients with Meniere's disease who had undergone surgery . Two articles included autopsy studies, and three articles studied polymorphisms using blood samples .…”
Section: General Characteristics Of Aquaporinsmentioning
confidence: 99%